The Mexican drug war: Elections and homicides - Aixa García-Ramos (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2022)
Mexico has experienced a dramatic increase in violence during the last decade. This increase has been associated with turf wars among Drug Trafficking Organisations (DTOs) for the control of strategic territories. This paper examines whether these territorial disputes are higher during the lame duck period, when incumbent DTOs might be relatively weaker. Using homicides as a proxy for turf wars, my results show support for this hypothesis. The increase in homicides is concentrated on municipalities in which the PRI wins the election. In contrast, those in which the PAN wins experience a decrease.
Keywords: D72; K42; 330; Organised crime; violence; elections